ISOLATION AND SCREENING OF FLOC-PRODUCING MICROORGANISMS - Milono Poesponegoro; Roy Heru Trisnamurti (Jurnal Kimia Terapan Indonesia, 1998)
All of the aerobic biological wastewater treatmenr systems depend upon the flocculation of the microorganisms and their separation from the liquid phase for complete stabilization. Therefore, aside from the metabolic characteristics of the microorganisms, the most important characteristic is their ability to flocculate.A study on the sludge .flocculation, isolation and screening of floc-producing microorganisms for biological wastewater treatment processes has been carried out. Microrganisms were olated from activated sludges obtained from local food industries. It was found that biofl occul ation of sludge was affected by the type and concentration of carbonaceous substrate. The substrates used were glucose, acetate and starch, at four levels of concentration, i.e. 1.0, 2.5, 5.0 and 25.0g/l. The activated sludge (Sludge-I) found better in bioflocculation than ther two sludge tested (Sludge-C and Sludge-K) was used for this purpose. The results showed that the Sludge-I gave better bioflocculation either on glucose or starch at a concentration of 1.0g/l than on acetate and other concentrations tested.The isolates (27 strains) obtainedfrom the activated sludge were then screened for their ability to flocculate and their acitivity in organic degradation. It showed that some of them produced good biofloc and gave high percentage of COD removal (more than 80%). The screening was carried out using shake-flask culture technique at 30°C for 10 days. Out of 27 strains tested, Strain-Ivb and Strain-Ivk were found suitable as inoculum candidates for the biological wastewater treatment since they produced granular floc which flocculated readily and gave high percentage of COD removal, around 85%, after 10 days of incubation. Tentatively both lsolate-Ivb and Isolate-Ivk have been identified as Candida sp.It was revealed that Strain-lvb and Str ain-Ivk gave better bioflocculation and percentage of COD removal, compared to 3 lands commercial inoculum tested. The commercial inocula produced pin-point floc with percentage of COD removal of 86 - 92%, while Strain-Ivb and Strain-Ivk produced granular floc with percentage of COD removal of 94% and 93% respectively. The results of study shows that continuous biological treatment of artificial wastewater containing starch (400 mg/l) using strainlvb gave percentage of COD removal of 77 - 96% (average value = 87%) at hydraulic retention time of 13 - 25 hrS (average value= 18 hrs); while strain-lvk gave percentage of COD removal of 84 - 95% (average value= 92%) at hydraulic retention time of 8 - 16 hrs (average value= 12 hrs). Both strains formed biofloc which settled readily.